(untitled) (Eurasian Journal of Ecology, 2019)
Spring waters, as natural discharges of groundwater to the surface, are an essential component of the natural environment. Spring water is considered by nature to be exceptionally pure, transparent, tasty, and balanced in its chemical composition, which makes it attractive to humans. However, the quality of spring water in urban areas has deteriorated significantly due to the high risk of chemical and bacterial contaminants entering groundwater. Therefore, studies were carried out of spring waters, actively consumed by the population of Almaty, for toxic and mutagenic activity. Spring 1 is located near the river Prohodnaya, bus stop number 28; spring 2 – on the road to the Big Almaty Lake, in front of the bridge over the river Ulken Almaty; spring 3 – near the river Batareika on the road to Kok-Zhailau; spring 4 – at the Prosveshchenets stop on the road to Medeu. The excess of MPC for lead in the water of springs 1, 3, and 4 has been established. Following the established MPC for heavy metals, water from spring 2 belongs to quality class 1 and is suitable for all types of water use; water from springs 1, 3 and 4 belongs to quality class 2. The waters of this water use’ class are suitable for all categories of water use, except for domestic. A bioluminescent test revealed high toxicity of spring waters 1-3, which significantly reduced the bioluminescent response of RecA and ColD biosensors (p <0.05). In the Allium test, the water of all the springs have phytotoxic activity, water from springs 1 and 3 also have a genotoxic effect. In the chromosomal aberration assay in H. vulgare, it was found that the water of spring-3 had a mutagenic activity. There was a statistically significant increase in the frequency of chromosomal aberrations in barley seeds (p <0.01). The remaining studied waters also increased the frequency of aberrant cells compared with the control; however, the difference was not statistically significant. Besides, polyploid cells (more than 1.5%) were identified with high frequency in the root meristem of barley seeds germinated in water from springs 1 and 3. The research indicates the presence of mutagenic factors in the waters of these springs. A comparative analysis of the level of contamination of the studied springs with heavy metals, the level of toxic and mutagenic activity of water allows ranking the investigated water objects in the following order: spring 3> spring 1> spring 2> spring 4. Key words: spring water, toxicity, mutagenicity, biosensor strains, heavy metals.